ANALISIS AKUNTANSI PIUTANG TAK TERTAGIH PADA KOPERASI USAHA MANDIRI BEKASI 2014 - Toni Triyulianto; Tavitri Rangkuti; Mukoronah Mukoronah (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
The role and contribution of cooperatives to the Indonesian economy is increasingly important because it brings changes in the economic structure. Macro can be seen, cooperatives are increasingly socializing and increasingly institutionalizing in the economy, increasing the benefits of cooperatives for society and the environment, a deeper understanding of the principles and joints of cooperatives and cooperative work procedures, increased production, income and welfare due to cooperatives, increased equity and justice through cooperatives, increased employment opportunities that exist because of cooperatives. This study discusses the process of recording accounts receivable and the method of eliminating uncollectible accounts for the Bekasi Independent Business Cooperative, by conducting interviews with the relevant employees and comparing them with available data. It turns out that the process of recording accounts receivable from the Mandiri Bekasi Business Cooperative uses a clean method and the method used to record the calculation of uncollectible receivables at the Bekasi Mandiri Business Cooperative uses the direct removal method.